Eu e os outros encenando vidas e transformando histórias através da consciência histórica, mito de Medeia e teatro do oprimido - Silva, Clécio Francisco de Albuquerque (2022)
The study “Me and Others Staging Lives and Producing Stories through Historical Awareness, Culture of Violence and the Culture of Peace at Maria Geny School” is based on the Professional Master's Program (ProfHistory) – at the Federal University of Paraíba, and at the School State Elementary and High School Teacher Maria Geny de Sousa Timóteo, from the State Education of Paraíba, involving the teaching-learning process of teachers and students in the production of historical knowledge. We prioritize the analysis of historical consciousness from the relationship between the culture of violence and the culture of peace, based on the study of Greek mythology, highlighting the pedagogical elements of the Myth of Medea in the relationship between Classical Greece and Contemporary Brazil through Theater of the Oppressed, used here as a tool for social, political, economic and cultural transformation. The product of the dissertation consists in the elaboration of a material for the study and formation of teachers, presenting the reading, interpretation and possibilities of transforming the culture of violence into a culture of peace of manifestations of social and school violence.